2000
DOI: 10.1007/s000660050002
|View full text |Cite
|
Sign up to set email alerts
|

Bestrahlung von Schädelbasistumoren mit Kohlenstoffionen bei der GSI Erste klinische Ergebnisse und zukünftige Perspektiven

Abstract: Clinical effectiveness and technical feasibility of this therapy modality could clearly be demonstrated in our study. To evaluate the clinical relevance of the different beam modalities studies with larger patient numbers are necessary. To continue our project a new heavy ion accelerator exclusively for clinical use is planned to be constructed in Heidelberg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(23 citation statements)
references
References 17 publications
1
17
0
5
Order By: Relevance
“…Initial results of this trial after treatment of 37 patients already indicated that carbon ion therapy yields results at least comparable to proton RT [6,39]. This report updates the treatment results after completion of patient recruitment in December 2001 in our phase I/II study.…”
Section: Introductionsupporting
confidence: 52%
“…Initial results of this trial after treatment of 37 patients already indicated that carbon ion therapy yields results at least comparable to proton RT [6,39]. This report updates the treatment results after completion of patient recruitment in December 2001 in our phase I/II study.…”
Section: Introductionsupporting
confidence: 52%
“…The advantage of SCRT compared to combined ventro-dorsal and lateral irradiation technique is significant for tumor coverage and simultaneous sparing of critical structures. New conformal techniques like intensity modulated radiation therapy or carbon ion irradiation [8] may achieve further gains in dose conformity and reduction of exposure of non-target structures and therefore improve the results in the treatment of this challenging tumor.…”
Section: Resultsmentioning
confidence: 99%
“…The other patients received adjuvant radiotherapy within 1-9 months after surgery (median 2 months). Due to availability in the past or tolerance of the individual mask fixation system the patients were treated either with conventional radiotherapy (6) or SCRT (8). The treatment was administered 5 days per week with 1.8 or 2 Gy single dose.…”
Section: Methodsmentioning
confidence: 99%
“…Bei der postoperativen Bestrahlung von Chordomen im Bereich der Wirbelsäule wird eine Dosis über 60 Gy angestrebt, um das Risiko der Rezidiventwicklung möglichst gering zu halten [2,6,8,15,18]. Dieser Dosisbereich überschreitet damit den Toleranzbereich sowohl des Myelons als auch der Cauda equina [7,20] Figures 3a and 3b.…”
Section: Introductionunclassified
“…Bedingt durch Artefakte bei der konventionellen CT und Verzerrungen bei der MRT ist eine präzise Abgrenzung zu Myelon und Cauda equina als Basis einer mög-lichen Bestrahlungsplanung oftmals kaum oder gar nicht möglich [4,26]. Selbst relativ metallartefaktinsensitive SE- [16,22] oder STIR-Sequenzen [23] in der MRTTechnik und neue CT-Protokolle [13] bieten in diesen Situationen bisweilen nicht ausreichend präzise Informationen über eine potentielle Tumorausdehnung in den Spinalkanal.Bei der postoperativen Bestrahlung von Chordomen im Bereich der Wirbelsäule wird eine Dosis über 60 Gy angestrebt, um das Risiko der Rezidiventwicklung möglichst gering zu halten [2,6,8,15,18]. Dieser Dosisbereich überschreitet damit den Toleranzbereich sowohl des Myelons als auch der Cauda equina [7,20].…”
unclassified